2010
DOI: 10.1007/s12291-010-0058-2
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Emblica officinalis Against Alcohol-Induced Hepatic Injury by Ameliorating Oxidative Stress in Rats

Abstract: The effect of Emblica officinalis fruit extract (EFE) against alcohol-induced hepatic damage in rats was investigated in the present study. In vitro studies showed that EFE possesses antioxidant as well nitric oxide (NO) scavenging activity. In vivo administration of alcohol (5 g/kg b.wt/day) for 60 days resulted increased liver lipid peroxidation, protein carbonyls, nitrite plus nitrate levels. Alcohol administration also significantly lowers the activities of superoxide dismutase, catalase, glutathione perox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(11 citation statements)
references
References 38 publications
3
8
0
Order By: Relevance
“…A recent clinical study showed that Amla extract improved endothelial function in patients with type 2 diabetes mellitus [ 3 ]. Furthermore, its antioxidant [ 4 ], hepatoprotective [ 5 ], nephroprotective [ 6 ], hypolipidemic [ 7 , 8 ], cardioprotective [ 9 , 10 ], and antidiabetic effects [ 11 ] were demonstrated in in vivo animal models. One potential mechanism for these effects was reduction of oxidative stress, based on observations of decreased oxidative stress with Amla treatment.…”
Section: Introductionmentioning
confidence: 99%
“…A recent clinical study showed that Amla extract improved endothelial function in patients with type 2 diabetes mellitus [ 3 ]. Furthermore, its antioxidant [ 4 ], hepatoprotective [ 5 ], nephroprotective [ 6 ], hypolipidemic [ 7 , 8 ], cardioprotective [ 9 , 10 ], and antidiabetic effects [ 11 ] were demonstrated in in vivo animal models. One potential mechanism for these effects was reduction of oxidative stress, based on observations of decreased oxidative stress with Amla treatment.…”
Section: Introductionmentioning
confidence: 99%
“…For example, quercetin prevents ethanol-induced dyslipidemia and mitochondrial oxidative damage [ 37 ]. Another report suggested that Emblica officinalis prevents ethanol-induced hepatic injury by ameliorating oxidative stress [ 38 ]. In this study, antioxidative functions in the liver of radon-inhaled and alcohol-administrated mice were significantly higher than in sham-inhaled and alcohol-administrated mice.…”
Section: Discussionmentioning
confidence: 99%
“…37 Damodara et al, also reported in their in vitro study that no scavenging compounds were present in Emblica officinalis, as this might protect from free radical-mediated oxidative stress in the hepatocytes of rats with alcohol stimulated liver damage. 38 Amla decreased autophagy presences through Beclin-1 and Bax/Bcl-2 down-regulation and decreased the level of N-nitrosodiethylamine-enhanced hepatic apoptosis. Thus, supplementation with amla counteracts N-nitrosodiethylamine stimulated liver damage through its anti-autophagy, anti-apoptosis, antioxidant and anti-inflammation characteristics.…”
Section: Emblica Officinalismentioning
confidence: 92%